NDT testing of stiffness evolution of UHPFRC since casting - Matos, Ana Mafalda (2017)
The current work presents the continuous monitoring of the early stiffness evolution of an UHPFRC (Ultra-high performance fibre reinforced cement composites) mixture using a combined set of non-destrutive testing techniques; "Elasticity Modulus Measurement through Ambient Response Method" (EMM-ARM), Ultra Sound Pulse (UPV) velocity measurement, and resistivity measurement. Three mixture proportions are considered for all testing techniques, covering a reference mixture without added fibres and a couple of mixes with 1.5 % and 3.0 % of fibres, respectively. Conclusions are taken in regard to the particularities of stiffness evolution in UHPFRC in of the particularities of the material (namely the presence of fibers).